Comparative Analyses of Child and Youth Services in Europe - Mike Seckinger (Social Work and Society)
This paper contains a comparative evaluation of the reactions of welfare states to the isomorphic pressures emanating from the European Union based on two case studies taken from the Child and Youth Welfare System. In the European Community different concepts of welfare policy exist. In the unification process every member state has to find answers to the pressure of assimilation invoked by the legislation. The objective of this explorative study is to show that countries can learn from each other in order to improve their own system of social services.